2001
DOI: 10.1093/ajcn/73.3.554
|View full text |Cite
|
Sign up to set email alerts
|

Dietary fat content alters insulin-mediated glucose metabolism in healthy men

Abstract: A high-fat, low-carbohydrate intake reduces the ability of insulin to suppress endogenous glucose production and alters the relation between oxidative and nonoxidative glucose disposal in a way that favors storage of glucose.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
98
3

Year Published

2002
2002
2014
2014

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(111 citation statements)
references
References 24 publications
10
98
3
Order By: Relevance
“…Both diets produced beneficial changes in the fasting blood lipid profile, plasma insulin and glucose. 12 .…”
Section: Nugenob Low-versus High-fat Diet M Petersen Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…Both diets produced beneficial changes in the fasting blood lipid profile, plasma insulin and glucose. 12 .…”
Section: Nugenob Low-versus High-fat Diet M Petersen Et Almentioning
confidence: 99%
“…10,11 The same changes in the diet induce a lowering of fasting plasma insulin concentrations, reflecting an increase in whole-body insulin sensitivity. 12 However, it is less clear which diet composition has the most beneficial effect during hypoenergetic dieting.…”
Section: Introductionmentioning
confidence: 99%
“…30 In the present study increased consumption of dietary fat did not lead to an increased insulin resistance index, which is consistent with findings in short term fat diet adaptation studies where peripheral insulin resistance was either unchanged 10,11 or only modestly increased. 12 In rodents there is evidence that inclusion of dietary n-3 fatty acids at least partly ameliorates the fat-diet-induced increase in insulin resistance. 31 In the present study the fat-rich diet had a reasonably high content of unsaturated fatty acids and n-3 fatty acids 32 and this may therefore be part of the explanation for the unchanged insulin resistance.…”
Section: Discussionmentioning
confidence: 99%
“…The BMI range of healthy subjects included in this review was 21-29kg/m 2 , and the age range was 26-55 years [8,9] . The diet macronutrient composition of the prescribed diets differed between studies.…”
Section: Healthy Weight Subjectsmentioning
confidence: 99%
“…Table 1 outlines the macronutrient composition of each study. Bisschop et al [8] used three study diets ranging from no fat (0%) to moderate (43%) and high (83%) fat content. After consumption of each diet for 11 days, it was found that the rate of fat oxidation during fasting was significantly higher after following the diet with 83% energy from fat compared to the other diets [8] .…”
Section: Healthy Weight Subjectsmentioning
confidence: 99%